Phrenology and Language. - Walker, Marian Niles (Verbatim: The Language Quarterly)
The article discusses the use of phrenology in determining the intellectual ability of an individual. It states the observation of German phrenologist, Franz Gall, relating an individual's physical characteristics, particularly the shape of the head and the eyes, with his intellect including his ability on language acquisition. It also mentions the physical ideal of a poet which includes an expansive forehead and large eyes.